Promoting EFL student's higher-order thinking skills through online learning - Rahmalia Anandayu, - (2022)
Studies on promoting students' higher-order thinking skills (HOTS) have been mostly carried out in traditional classroom settings, but there are still few studies regarding the issue through online teaching. This study investigated how HOTS were promoted in the online setting that involved two high school English teachers. Data of this study were generated from semi-structured interviews of teachers, classroom observations, and document analysis. The study used revised Bloom's taxonomy (Anderson et al., 2001) to analyse the data. The study found out teachers implemented inquiry learning method to promote HOTS as it provided students with time and space to analyse texts. To assist students' understanding of concept and contexts, pictures and questioning were presented. HOTS were also promoted through higher-level questions that involved analysing and evaluating items in the assessment process. Unfortunately, the teachers still had difficulty to promote HOTS in grammar lesson. The challenges on promoting HOTS in online learning were related to three aspects, namely students, teachers, and technical problems. The study also offers pedagogical implications as well as suggestions for future research.